Postural control in aging: a comparative study among Brazil and Spain - Alfieri, Fábio Marcon; Riberto, Marcelo; Ribeiro, Carla Paschoal Corsi; Carreres, Maria Àngels Abril; Battistella, Linamara Rizzo; Figuera, Roser Garreta (Acta Fisiátrica, 2009)
Aging cause changes in the sensory and musculoskeletal systems, which together affect the postural control of the elderly. The aim of this study was to assess and compare the postural control of elderly individuals in São Paulo, Brazil, with elderly individuals who live in Terrassa (Barcelona), Spain. A total of 36 elderly Brazilian individu-als (mean age: 69.61 ± 5.3 years) and 33 elderly individuals from Spain (69.72 ± 4.6 years) participated in the study; they were consid-ered to be healthy and were recruited from two rehabilitation services. The volunteers underwent postural control assessment through the Timed Up and Go and the Guralnik Test Battery tests. Data were analyzed using the t test. The results showed that the groups were similar regarding age and body composition, but the group in Brazil showed better results at both evaluations, when compared with the group in Spain. We concluded that Brazilian individuals in this series showed a better performance on the postural control tests.